The Role Of Operant Conditioning In Enhaching Learning Outcomes In Social Studies Education - Pradika Rakasiwy, Mochamad Randy; Surya Cipta, Viona Dea; Nur Fadhilah, Nanditas Adhys (Program Studi Pendidikan IPS Unesa, 2025)
This research addresses the problem of students’ low interest in social studies, which is often perceived as overly theoretical, monotonous, and lacking relevance to everyday life. These perceptions contribute to low motivation and limited student participation during learning activities. The purpose of this study is to examine the effectiveness of integrating an operant conditioning approach into social studies learning to improve academic achievement. The study employed a quasi-experimental method with a pretest-posttest control group design, involving two junior high school classes. The experimental group received treatment through the application of reward and punishment strategies based on operant conditioning principles, while the control group underwent conventional instruction. Results showed a significant increase in academic achievement in the experimental group compared to the control group. These findings indicate that reinforcement-based learning can effectively enhance students' motivation and academic performance in social studies. The implication of this study highlights the value of incorporating psychological approaches into teaching strategies. Applying operant conditioning can help teachers create a more conducive and engaging learning environment, encouraging student participation and supporting better learning outcomes. Therefore, behaviorist strategies, particularly reinforcement, are recommended as a practical approach to address motivational issues in social studies education.